BPE-P04: the effect of plant oils for submerged fermentation of Schizophyllum commune producing mycelium biomass and exopolysaccharides - Abdul Halim, Khairul Hazwat; Mohd Kamal, Irnada Syuhaidah; Mohd Nor Rashid, Noraswati; Mel, Maizirwan (2012)
The effect of plant oils (olive, palm, corn, sunflower and soya bean) addition at different concentrations (0.5%. 1.0%, 2.0% and 4.0%) producing mycelium biomass (MBS) and exopolysaccharides (EPS) in submerged fermentation using a local strain Schizophyllum commune was determined. Additional of all type of plant oils exhibit higher yield of MBS and EPS than without plant oils. The highest production of MBS was obtained at 26.08 g/L in 4.0% palm oil, while in control (without plant oils) gave only 12.16 g/L of MBS. The maximum concentration of EPS was produced is 2.2 g/L from medium containing 1.0% and 4.0% of olive oil; and 2.0% of sunflower oil. The best treatment containing 4.0% of corn oil was selected since it showed high production of MBS (23.44 g/L) and EPS (2.1 g/L) compared to other treatments. However, the addition of 4.0% of palm oil in submerged culture of local strain Schizophyllum commune was preferred since it also showed the good result on production of MBS (26.08 g/L) and EPS (2.0 g/L). Palm oil is locally source and cheap, therefore, the MBS can be produced in local industry with cost-effective. The MBS will be used as liquid spawn (seed) or extraction of bioactive compounds in pharmaceutical industry.